Three new species of the plume moths (Lepidoptera: Pterophoridae) from Colombia Part 2 - Kovtunovich, Vasily; Ustjuzhanin, Petr (Zootaxa, 2025)
Three new species of plume moths (Lepidoptera, Pterophoridae) from Colombia are described: Postplatyptilia storozhenkoi Kovtunovich & Ustjuzhanin, sp. nov., Stenoptilodes bernali Kovtunovich & Ustjuzhanin, sp. nov., and Hellinsia fatherzosima Kovtunovich & Ustjuzhanin, sp. nov.